IMPACT OF CORONA VIRUS ON THE TRADE SECTOR IN INDONESIA - Simbolon, Rinaldo (Jurnal Kompetitif Bisnis, 2020)
Abstract Today the world is shocked by the spread of the corona outbreak virus that originated in China. As a result of this virus, many residents of China and many other countries have died. The Chinese economy has fallen from companies that have to close. Given that China is the country with the largest economy in the world and Indonesia’s main trading partner, the disruption of the Chinese economy will affect the world economy including Indonesia. This paper examines the impact of viruses on Indonesia’s growth. The most dominant impact occurs on trade. During January 2020, there was a drastic reduction in exports of imports from and to China. Related to the efforts that can be made to overcome them, among other diversifications, export exports to other countries; increase domestic production and consumption; and increasing domestic and foreign tourists.